Biophysical Applications of Satellite Remote Sensing - Hanes, Jonathan M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
A variety of biophysical applications (e.g. leaf area index and gross primary productivity) have been derived from measurements of the Earth system obtained remotely by NASA$1 (Bs MODIS sensors and other satellite platforms. In Biophysical Applications of Satellite Remote Sensing, the authors describe major applications of satellite remote sensing for studying Earth's biophysical phenomena. The focus of the book lies on the broad palette of specific applications (metrics) of biophysical activity derived using satellite remote sensing. With in-depth discussions of satellite-derived biophysical metrics that focus specifically on theory, methodology, validation, major findings, and directions of future research, this book provides an excellent resource for remote sensing specialists, ecologists, geographers, biologists, climatologists, and environmental scientists.s
Keywords: Geography; Remote sensing; Environmental sciences; Geography; Remote Sensing/Photogrammetry.; Biophysics and Biological Physics; Environment, general